FORMS, SPACES AND TIMES OF MARGINALITY AN INTRODUCTION - Silvia Aru; Matteo Puttilli (Bollettino della Società Geografica Italiana)
The paper introduces seven contributions resulting from the sixth Italian and French Seminar of Social Geography with the title: «Spatial Justice – Marginality, Isolation, Citizenship». The first part explores the different viewpoints and approaches to marginality within the international debate, focusing on the socio-spatial effects of the processes of marginalization. The second part presents the most recent reflections upon the multiple and controversial connections between contemporary marginalizations and neoliberal (urban) policies. The concluding part stresses the urgency for new empirically oriented and spatially differentiated researches in the field of socio-spatial marginality and socio-spatial justice.